Elevated Cardiac Troponin I following Asymptomatic Intradialytic Hypotension: A Pilot Study with a 2-Year Follow-Up. (1st August 2022) - Alirezaei, Toktam; Jebreil Moosavi, Mir Jafar; Irilouzadian, Rana; Taziki, Elahe
Abstract : Background . Intradialytic hypotension (IDH) has been recognized as a serious and frequent complication during hemodialysis (HD) of end-stage renal disease (ESRD) patients, but the effect of asymptomatic IDH on cardiac troponin I (cTnI) levels is not definitively elucidated. Methods . 70 asymptomatic HD patients with negative predialysis cTnI were included. They were on maintenance HD thrice weekly. All patients were monitored during the HD session for hemodynamic changes and symptoms related to IDH. Patients were followed for two years, and their outcomes are noted as an acute coronary syndrome (ACS), cardiac death, no ACS, noncardiac death, and kidney transplant. Results . Compared with the baseline blood pressure values, there was a drop in systolic blood pressure for all subjects, but according to the 2007 European Best Practice Guidelines on hemodynamic instability, asymptomatic IDH was defined in 27 (38.6%) patients. The results demonstrated a significant correlation ( r  = 0.492) (p < 0.05 ) between asymptomatic IDH and elevated postdialysis levels of cTnI. In 2-year follow-up of patients, ACS and cardiac death happened more in patients with elevated cTnI. Conclusion . The results of our study suggest that asymptomatic IDH affects cTnI levels. Given that cTnI is a marker of myocardial damage and a predictor of cardiovascular mortality in ESRD patients, these findings recommend that considering the asymptomatic decrease in blood pressure levels during HD is very important and critical.